ANALISIS ASOSIATIF PENGARUH RATIO SOLVABILITAS DAN EFISIENSI BIAYA OPERASIONAL TERHADAP PROFITABILITAS PERUSAHAAN PADA PT.PERUSAHAAN GAS NEGARA TBK - Lestari, Dinda; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the associative effect of solvency ratios and operational cost efficiency on the profitability of PT Perusahaan Gas Negara Tbk (PGAS) during the 2018–2023 period. A quantitative approach using multiple linear regression was applied, with secondary data obtained from the company’s annual financial reports published on the Indonesia Stock Exchange (IDX). The independent variables include solvency ratios (measured by Debt to Equity Ratio/DER and Debt to Asset. Ratio/DAR) and operational cost efficiency (measured by Operating Expense Ratio/OER), while the dependent variable is profitability (measured by Return on Assets/ROA).The results indicate that solvency ratios have a significant negative effect on profitability (regression coefficients: DER: -0.245, p<0.05; DAR: -0.312, p<0.01), whereas operational cost efficiency has a significant positive effect (OER coefficient: 0.418, p<0.01). Simultaneously, both independent variables explain 72.5% of the variation in profitability (R² = 0.725).These findings imply that prudent debt management and optimization of operational costs are crucial for improving PGAS profitability amid global gas price fluctuations. Recommendations include diversifying financial strategies and enhancing supply chain efficiency to ensure sustainable financial performance.